Analysis of Deixis in Lavender Haze Taylor Swift's Song Lyrics - Nurjannah; Saerudin, Sahur (Cognitive Development Journal, 2024)
Deixis is a linguistic phenomenon that is very important in the study of pragmatics. This research aims to identify types of deixis and references in Taylor Swift's song Lavender Haze. This research uses a qualitative descriptive method and a pragmatic approach. Data collection is carried out by searching, selecting, reading, identifying and coding, then analyzing the data by presenting, describing, interpreting and concluding. The author found types of deixis, namely person deixis, spatial deixis, temporal deixis, and discourse deixis. The author concludes that the song lyrics use types of deixis where personal deixis, especially first person deixis, always appears in the five song lyrics which tell the life story of the songwriter himself. In other words, the use and meaning of deixis based on the context of the song lyrics as a whole can provide information about people, places, times and discourse. As well as, connecting utterances with time and space relationships and is useful for capturing referential meaning which includes who, where and when the utterance was uttered. This research provides an important contribution in understanding the use of deixis in song lyrics, as well as revealing the referential meaning and broader context in the song Lavender Haze by Taylor Swift.